A Fully Conjugated Porphyrin‐[36]Octaphyrin‐Porphyrin Hybrid Tape Exhibiting Möbius Aromaticity. Issue 20 (10th March 2022) - Nakai, Akito; Tanaka, Takayuki; Osuka, Atsuhiro
Abstract: Directly meso ‐ meso linked porphyrin‐tetrabromo[36]octaphyrin‐porphyrin hybrid trimer 10 was successfully synthesized via acid‐catalyzed condensation reaction and subsequent oxidation. Zn II ‐metalation of 10 induced transannular meso‐meso bond formation to give Möbius aromatic bis‐Zn II octaphyrin 11, which was oxidized by DDQ/Sc(OTf)3 to provide fully conjugated porphyrin‐[36]octaphyrin‐porphyrin hybrid tape 12 as the first example of porphyrin tape exhibiting Möbius aromaticity. Hybrid tape 12 displays significantly red‐shifted absorption and small electrochemical HOMO‐LUMO gap, indicating the effective conjugation through the whole chromophores. Abstract : Oxidative fusion of meso ‐ meso linked porphyrin‐bis‐Zn II [36]octaphyrin‐porphyrin hybrid trimer afforded a triply‐linked hybrid tape as the first example of porphyrin tapes exhibiting Möbius aromaticity. The electronic conjugation was fully extended over the whole molecule, showing red‐shifted absorption up to 1274 nm. The extent of electronic perturbation was compared with planar porphyrin‐[26]hexaphyrin‐porphyrin hybrid tape to illuminate the consequence of twisted π‐surface. A Fully Conjugated Porphyrin‐[36]Octaphyrin‐Porphyrin Hybrid Tape Exhibiting Mobius Aromaticity (Tanaka, Osuka et al.)